Rumor and communication in Asia in the Internet age - Dalziel, Greg (Media, culture, and social change in Asia series ;, 2013)
"Explores how rumours are created, disseminated and absorbed in the age of the internet and mobile communications. It includes a wide range of examples and, besides considering the overall processes involved, engages with scholarly debates in the field of media and communication studies"--